Konsep Moderat Dalam Islam Nusantara: Tinjauan Terhadap QS. Al-Baqarah [2]: 143 - Nurlaila Radiani; Ris'an Rusli (Jurnal Semiotika Quran, 2021)
Islam Nusantara is a theme that until now still has a big question mark and debate among Islamic thinkers. This paper reviews the concept of moderation in Islam Nusantara with a review of QS. al-Baqarah [2]: 143. By using the descriptive-interpretative method, it is concluded that moderate Islam in Nusantara explains the existence of Islamic moderation which is very appropriate to become wasathiyah by preserving local traditions in the archipelago. The purpose of this moderation of Islam Nusantara is to maintain tolerance and peace in the archipelago. The role of moderation means that Islam has completed the religion of all religions, in the sense that Islam is a religion brought by the Prophet as compassion for the world which is contained in moderation, tolerance, and peace, for all mankind.